Contribution to the flora of the Selvagens archipelago (Portugal) (I) - Menezes de Sequeira, Miguel Pinto da Silva; Góis-Marques, Carlos; Gouveia, Manuela; Zino, Francis; Bairos, Célia; Mesquita, Sandra; Capelo, Jorge (Botanica Complutensis, 2023)
Plant specimens obtained by the authors from several expeditions to the Selvagens Islands (2004-2021), complemented by the study of herbarium specimens, led to the identification of several new species records for the Selvagens archipelago, namely the taxa currently considered as Canary Islands endemics Trisetaria lapalmae and Polycarpaea divaricata. Other new taxa records for the Selvagens Islands include Convolvulus siculus subsp. elongatus and the grasses Bromus rigidus and Phalaris minor. Notes on Misopates salvagense, Asplenium marinum, Spergularia diandra and Rostraria pumila are also included. Comments on taxa include distribution, ecology, taxonomy, nomenclature, conservation, and historical data. Results are discussed in the light of habitat restoration, following Nicotiana glauca near eradication and rodent eradication. These aspects are also discussed considering the historical evolution of knowledge on the Selvagens vascular flora.